ASPECTS OF THE OPERATION OF INNOVATIVE COMPANIES ON THE EXAMPLE OF EASTERN POLAND - Koza, Iwona (Management and Administration Journal, 2021)
Innovativeness is the subject of numerous studies in which researchers look for its conditions, causes and effects. The innovation process begins even before the commencement of scientific research in the enterprise, at the stage of creating an idea, and ends with the implementation of innovation and its dissemination. It is better to construct a wide range of indicators relating to the conditions or the determinants of functioning of innovative companies, including issues, such as, entrepreneurship, technological development and diversity. Particularly interesting can be a specification of these aspects in relation to Eastern Poland - a region with unfavorable conditions for business development because of insufficiently developed economic base, as well as underdevelopment of transport, economic and human resources infrastructure and local market.